Are There Price Asymmetries in the U.S. Beef Market? - Bachmeier, Lance J.; Pozo, Veronica F.; Schroeder, Ted C. (My University, 2020)
We examine price transmissions among farm, wholesale and retail U.S. beef markets using two types of retail price data, one collected by the Bureau of Labor Statistics (BLS), and the other one collected at the point of sale using electronic scanners. Using a test based on the simulation of nonlinear impulse response functions, we find no evidence of vertical asymmetric price transmissions in models estimated using scanner data. However, prices adjust asymmetrically in models estimated using BLS data. Because scanner prices are more reflective of actual consumer purchases, the U.S. beef market is not as inefficient as previous studies suggest.
Keywords: Price Asymmetry; BLS Prices; Scanner Prices; Nonlinear Impulse Response Functions; Beef Market; Threshold Vector Error Correction Models